The Combination of NLR and D-dimer as Predictor Instrument for the Severity of COVID-19 - Shofia Widya Murti; Delita Prihatni; Adhi Kristianto Sugianli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Coronavirus Disease-19 (COVID-19) is caused by Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS-CoV-2). In severe cases, the immune response may cause a cytokine storm. Neutrophil Lymphocyte Ratio (NLR) and D-dimer are parameters that may be used to predict the severity of COVID-19. This study aims to determine the diagnostic validity of the combination of NLR and D-dimer on the severity of COVID-19 patients. The study population was hospitalized COVID-19 patients whose diagnosis were confirmed by real time-PCR. This was a retrospective cross-sectional study. The cut-off value was based on the Area Under Curve (AUC) of the Receiver Operator Characteristic Curve (ROC) analysis and the combination of NLR and D-Dimer validity was tested against the severe and non-severe COVID-19 groups by assessing sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), positive Likelihood Ratio (LR+) and negative Likelihood Ratio (LR-). There were 1,314 subjects. Seven hundred and forty-four were in the severe group, 570 in the non-severe group. The combination of NLR > 4.02 and D-dimer > 1.12 mg/L on the severity of COVID-19 showed a sensitivity value of 70.8%, specificity 98.3%, PPV 98.1%, NPV 72.1%, LR+ 40.38 and LR- 0.30. The combination of NLR >4.02 and D-dimer >1.12 mg/L for the severity of COVID-19 showed high specificity and PPV (98.3% and 98.1%). This was also supported by the LR+ value, which indicates that if NLR > 4.02 and D-dimer > 1.12 mg/L, it may cause severe COVID-19 by 40.38 times compared to NLR â‰¤4.02, and D-dimer â‰¤1.12 mg/L. The combination of NLR and D-Dimer can be used to predict the severity of COVID-19.